Pengaruh Penggunaan Media Pembelajaran Online Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran IPS Terpadu Kelas VII di SMP Negeri 1 Telaga Kabupaten Gorontalo - Karmila Abd. Razak; Sudirman (Yayasan Pendidikan Sudirman Mandiri, 2024)
This study aims determine the effect of online learning media on seventh-grade students' learning motivation in integrated social studies subjects at SMP state junior high school in Telaga, Gorontalo Regency. Furthermore, this quantitative correlational research employed a descriptive quantitative approach. Likewise, It employed primary data obtained from distributing questionnaires. The sampling in this study used the Slovin formula, with the number of samples in this study amounting to 26 respondents. The data were further analyzed by simple linear regression with SPSS 21 program. The results show that online learning media have a positive and significant effect on students' learning motivation, which means that the better the use of online learning media will increase students' learning motivation The coefficient of determination shows that as many as 74.1% of the learning facihries can explain the variability of students' learning outcomes.